2014
DOI: 10.1016/j.neuroscience.2014.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ACE2/Ang-(1–7)/Mas pathway reduces oxygen–glucose deprivation-induced tissue swelling, ROS production, and cell death in mouse brain with angiotensin II overproduction

Abstract: We previously demonstrated that mice which overexpress human renin and angiotensinogen (R+A+) show enhanced cerebral damage in both in vivo and in vitro experimental ischemia models. Angiotensin converting enzyme 2 (ACE2) counteracts the effects of angiotensin (Ang-II) by transforming it into Ang-(1-7), thus reducing the ligand for the AT1 receptor and increasing stimulation of the Mas receptor. Triple transgenic mice, SARA, which specifically overexpress ACE2 in neurons of R+A+ mice were used to study the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 93 publications
4
57
0
Order By: Relevance
“…This hypothesis is supported by findings from multiple groups that axis activation resulted in upregulation of endothelial NOS (eNOS) and NO production in stroke [28,29, 30•, 54, 55], as well as improved endothelial function in spSHRs [56, 57]. It was very recently demonstrated that application of Ang-(1-7) into the RVLM resulted in complete attenuation of the detrimental stroke-induced pressor response as well as preventing increased heart rate [19].…”
Section: Mechanisms Of Ang-(1-7)-induced Neuroprotectionmentioning
confidence: 64%
See 2 more Smart Citations
“…This hypothesis is supported by findings from multiple groups that axis activation resulted in upregulation of endothelial NOS (eNOS) and NO production in stroke [28,29, 30•, 54, 55], as well as improved endothelial function in spSHRs [56, 57]. It was very recently demonstrated that application of Ang-(1-7) into the RVLM resulted in complete attenuation of the detrimental stroke-induced pressor response as well as preventing increased heart rate [19].…”
Section: Mechanisms Of Ang-(1-7)-induced Neuroprotectionmentioning
confidence: 64%
“…Our group first used an ischemic stroke model of endothelin-1 (ET-1)-induced MCAO and found that rats that were infused centrally via the intracerebroventricular (ICV) route with Ang-(1-7) performed better on neurological function testing and had an ~50 % reduction in infarct sizes [24••, 25], which was prevented by co-administration of the Mas antagonist A-779, findings that have subsequently been verified in models of permanent MCAO [26, 27••]. In a study using AngII-overexpressing mice subjected to permanent focal ischemic stroke, neuronal ACE2 overexpression resulted in similar cerebroprotection in vivo [28] and in vitro [29]. Additionally, lentiviral ACE2 priming of endothelial progenitor cells enhanced the ability of these cells to reduce infarct size and improve neurological function [30•].…”
Section: The Angiotensin-(1-7)–mas Axis and Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the latter pathway, the ACE2/Ang‐(1–7)/Mas axis, has indeed shown therapeutic promise in both ischaemic and haemorrhagic strokes, according to studies from independent groups of investigators using different models of stroke induction, as recently reviewed (Gironacci, Cerniello, Longo Carbajosa, Goldstein, & Cerrato, ; Regenhardt, Bennion, & Sumners, ). In each of those studies, Ang‐(1–7) was infused directly into the brain via the intracerebroventricular route, to circumvent the blood–brain barrier (Chen et al., ; Jiang et al, ; Jiang et al., ; Lu et al, ; Mecca et al., ; Regenhardt et al., ; Regenhardt & Mecca, et al., ; Zheng, Li, Chen, Bihl et al., ; Zheng, Li, Chen, Wang et al., ). Furthermore, intracerebroventricular infusion of the ACE2 activator diminazine aceturate (DIZE) also elicited significant neuroprotection (Mecca et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ang-(1-7) induces regional and systemic vasodilation, diuresis and natriuresis, and also has antiproliferative and antimigratory effects on smooth muscle cells, cardiomyocytes, fibroblasts and glomerular cells. The cardioprotective effects of Ang-(1-7) are mediated by MasR to different signaling pathways involving MAPK, phosphoinositide 3-kinase (PI3K)/Akt and NADPH oxidase [Nemoto et al 2014;Zheng et al 2014]. The interaction Ang-(1-7)/MasR leads to activation of different effectors such as forkhead box protein O1 (FOXO1), COX-2 and vasodilator mediators such as prostanoids and NO.…”
Section: Ang-(1-7)mentioning
confidence: 99%